The ability of an electrocardiogram to predict fatal and non-fatal cardiac events in asymptomatic middle-aged subjects. (2nd October 2016) - Terho, Henri K.; Tikkanen, Jani T.; Kenttä, Tuomas V.; Junttila, M. Juhani; Aro, Aapo L.; Anttonen, Olli; Kerola, Tuomas; Rissanen, Harri A.; Knekt, Paul; Reunanen, Antti; Huikuri, Heikki V.
Abstract: Introduction: The long-term prognostic value of a standard 12-lead electrocardiogram (ECG) for predicting cardiac events in apparently healthy middle-aged subjects is not well defined. Materials and methods: A total of 9511 middle-aged subjects (mean age 43 ± 8.2 years, 52% males) without a known cardiac disease and with a follow-up 40 years were included in the study. Fatal and non-fatal cardiac events were collected from the national registries. The predictive value of ECG was separately analyzed for 10 and 30 years. Major ECG abnormalities were classified according to the Minnesota code. Results: Subjects with major ECG abnormalities (N = 1131) had an increased risk of cardiac death after 10-years (adjusted hazard ratio [HR] 1.7; 95% confidence interval [95% CI], 1.1–2.5, p = 0.009) and 30-years of follow-up (HR 1.3, 95% CI, 1.1–1.5, p < 0.001). Model discrimination measured with the C-index showed only a minor improvement with the inclusion of ECG abnormalities: 0.851 versus 0.853 and 0.742 versus 0.743 for 10- and 30-year follow-up, respectively. ECG did not predict non-fatal cardiac events after 10-years or 30-years of follow-up. Discussion: Major ECG abnormalities are associated with an increased risk of short and long-term cardiac mortality in middle-aged subjects. However, the improvement in discrimination between subjects with and without fatal cardiac events was marginal with abnormal ECG. KEY MESSAGES: Abnormalities observed on 12-lead electrocardiogram are shown to have prognostic significance for cardiac events in elderly subjects without known cardiac disease. Our results suggest that ECG abnormalities increase the risk of fatal cardiac events also in middle-aged healthy subjects.